Ayurveda As An Adjuvant Therapy In Mild To Moderate Covid19 Symptoms - Verma, Deepak; Shukla, Megha (International Research Journal of Ayurveda & Yoga, 2021)
In the last 20 years, most of the world affected due to several epidemic or pandemic; Out of them originated from a virus have higher mortality and spread frequency. The COVID-19 pandemic, also known as the coronavirus pandemic, is an ongoing global pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Most people infected with the COVID-19 virus will experience mild to moderate respiratory illness and recover without requiring special treatment. According to the University of Washington’s Institute for Health Metrics and Evaluation, "the number of cases that are being detected needs to be multiplied by 20 or more to get the number of infections that are occurring in India." The institute reportedly also projected that India will report over 1 million (10 lakh) deaths by the start of August. The cumulative death toll due to COVID-19 could rise to 6,65,000 by the end of July, with around 3,29,000 additional deaths between April 12 to August 1 2021. An ayurvedic approach towards the prevention and management; to avoid severe complications in early stage of infection would be beneficial as adjunct therapy. A better lifestyle, knowledge of food and nutrition, immune boosters, prophylactic medication and adjunct therapy can definitely help to the health system of India. Most of the time Ayurveda could not advice because of their metal substances so all the medical professionals can advice plant based compounds as precaution. This review sheds light on the current SARS-CoV-2 pandemic, epidemiology, global status and possible ayurvedic rural treatment strategies with future potential.